ROBOTICS AS A MEANS OF TRAINING OF FUTURE TEACHERS OF NATURAL AND MATHEMATICAL DISCIPLINES - Valko , Н. В. (Journal of Information Technologies in Education (ITE), 2019)
The article is devoted to the use of robotics as a means of training future teachers to use STEMtechnologies in professional activities. The introduction of integrative courses in the study of biology, physics and chemistry requires special training of teachers of natural and mathematical disciplines to form their relevant competencies. Educational robotics, in our opinion, is combined with the study of basic disciplines, is an innovative tool for understanding the integrativity of objects. In a broader sense, robotics is the basis for the perception and support of the social potential of technology, and consequently, the raising of the prestige of the scientific and technological direction of development in society. The study examined curricula for secondary schools from school chemistry courses (grades 7-9), physics (grades 7-9), and biology (grades 6-9). The content of the training materials in these subjects contains hours for the implementation of project activities, which is based on the formation of holistic ideas about the laws of development of science and technology. In the work, we identified topics for each subject that can be implemented using robotics, provided examples of such projects, and also indicated the stages of their creation. In contrast to the prevailing opinion about a robotic project, as a project only on information technology or physics, an example of the transfer of knowledge in physics, chemistry and biology at different stages of the creation of such systems is given. The competencies that are formed as a result of the implementation of STEM-projects in robotics, as well as the types of activities that affect their formation, are determined. An example of the relationship between various activities in STEM-projects on robotics is given. in the process of preparing future teachers of natural mathematical disciplines. This material will help future and practicing teachers in planning their own and student activities to create robotic systems.